Preoperative metabolic acidosis and acute kidney injury after open laparotomy in the neonatal intensive care unit. Issue 10 (30th October 2019) - Yum, Sook Kyung; Seo, Yu Mi; Youn, Young‐Ah; Sung, In Kyung
Abstract: Background: This study evaluated potential risk factors associated with acute kidney injury (AKI) in infants undergoing bedside open laparotomy in the neonatal intensive care unit (NICU), and analyzed the association between postoperative AKI and outcomes. Methods: Retrospective data, including neonatal characteristics, perioperative findings (i.e. vital signs and fluid status), postoperative AKI incidence, and postoperative mortality rate of infants who underwent bedside open laparotomy in the NICU between May 2013 and May 2018 were collected and analyzed. Results: A total of 53 cases (26 in AKI group vs 27 in non‐AKI group) were analyzed. On univariable analysis, transfusion, pre‐ and postoperative blood gas analysis and number of inotropic agents, cumulative postoperative percentage fluid overload (48 h), and preoperative hourly urine output were associated with the development of postoperative AKI. On multivariable logistic regression analysis, preoperative acidosis (pH <7.15 or base deficit >10; P = 0.002; OR, 11.067; 95%CI: 2.499–49.017) and preoperative urine output ( P = 0.035; OR, 0.548; 95%CI: 0.314–0.959) were significant factors associated with postoperative AKI. Postoperative mortality rate 30 days after surgery was higher in the AKI group, but the difference was not significant. Conclusions: Preoperative metabolic acidosis and urine output are important factors potentially associated with the development of postoperative AKI in neonates undergoing bedside open laparotomy. Strategies such as alkali therapy, which protect the kidney from further injury, should be validated in future studies. A decreasing urine output may suggest deteriorating kidney function prior to surgery, potentially amplifying the risk of postoperative AKI.